Performing central venous catheters in neonates and small infants undergoing cardiac surgery using a wireless transducer for ultrasound guidance: a prospective, observational pilot study - Judith Schiefer; Paul Lichtenegger; Daniel Zimpfer; Doris Hutschala; Lorenz Kuessel; Alessia Felli; Stephan Hornykewycz; Peter Faybik; Eva Base (BMC, 2021)
Abstract Background Neonates and small infants with congenital cardiac disease undergoing cardiac surgery represent major challenges facing paediatric anaesthesia and perioperative medicine. Aims. We here aimed to investigate the success rates in performing ultrasound (US) guided central venous catheter insertion (CVC) in neonates and small infants undergoing cardiac surgery, and to evaluate the practicability and feasibility of thereby using a novel wireless US transducer (WUST). Methods Thirty neonates and small infants with a maximum body weight of 10 kg and need for CVC before cardiac surgery were included in this observational trial and were subdivided into two groups according to their weight: < 5 kg and ≥ 5 kg. Cannulation success, failure rate, essential procedure related time periods, and complications were recorded and the clinical utility of the WUST was assessed by a 5-point Likert scale. Results In total, CVC-insertion was successful in 27 (90%) of the patients and the first attempt was successful in 24 (78%) of patients. Success rates of CVC were 80% < 5 kg and 100% ≥5 kg. Comparing the two groups we found a clear trend towards longer needle insertion time in patients weighing < 5 kg (33 [28-69] vs. 24 [15-37]s, P = .07), whereas, the total time for catheter insertion and the duration of the whole procedure were similar in both groups (199 [167-228] vs. 178 [138-234] and 720[538-818] vs. 660 [562-833]s. In total, we report 3 (10%) cases of local hematoma as procedure-related complications. Assessments of the WUST revealed very good survey results for all parameters of practicability and handling (all ratings between 4.5 and 5.0). Conclusion Although difficulties in CVC-placement seem to relate to vessel size and patient's weight, US guided CVC-insertion represents a valuable, fast, and safe intervention in neonates and small children undergoing cardiac surgery. Using the WUST is feasible for this clinical application and may aid in efforts aiming to optimize perioperative care. Trial registration Wireless US-guided CVC placement in infants; Clinicaltrials.gov: NCT04597021 ; Date of Registration: 21October, 2020; retrospectively registered.